Closed reduction of zygomatic arch fractures using a Tubbs-Logan mitral valve dilator - Yontar, Yalçın; Tatar, Sedat; Baykan, Halit (ENT Updates, 2020)
Objective: To present technical details and experiences regarding the use of a Tubbs-Logan mitral valve dilator for the closed reduction of zygomatic arch fractures. Method: Over a period of about three years, closed reduction was indicated and performed in 22 patients with a zygomatic arch fracture. In all patients, depressed fracture segments were reduced using a Tubbs-Logan mitral valve dilator via the Gillies’ temporal approach. Results: The majority of the injuries were due to motor vehicle collisions (n=8, 36.4%). The zygomatic arch fracture was isolated in 12 patients (54.5%). However, it was a component of a zygomatic complex fracture in 10 patients (45.5%). Of those, rigid internal fixation of the zygomatic body was performed in 8 and the zygomatic body was only closely reduced by a bone hook in 2 patients. Repair of a concomitant orbital floor fracture was performed in 2, a mandibular angle fracture in 1 and a frontal sinus fracture in 1 patient. The reduction status of the zygomatic arch was excellent in 12 (54.5%), good in 8 (36.4%) and fair in 2 patients (9.1%). During the follow-ups, no functional or cosmetic sequelae regarding repaired fractures of the zygomatic arch, zygomatic body or other facial bones were recorded. Conclusion: We suggest that the Tubbs-Logan mitral valve dilator is a safe and effective alternative in terms of closed reduction of zygomatic arch fractures, whether they are isolated or not. We think that further ergonomic modifications would be beneficial to improve the positioning of the instrument in restricted areas observed due to severe depression of the zygomatic arch.